Sheath blight of rice: current status and perspectives - P. KUMAR, RAM SINGH*, S. SUNDER and (Indian Phytopathology, 2016)
Sheath blight of rice caused by Rhizoctonia solani Kuhn [teleomorph: Thanatephorus Â cucumeris (Frank) Donk] is of worldwide occurrence and is known to cause substantial yield losses. It is a major production constraint in high yielding varieties under intensive rice production systems. The pathogen has a very wide host range and exhibits considerable pathogenic and molecular variability. Due to non-availability of resistant cultivars, the management of sheath blight primarily relies on chemical control. However, the disease can be managed effectively through integration of effective cultural practices, botanical pesticides, bio-control agents and fungitoxicants. In this article, the information available on various aspects of this disease has been presented and discussed alongwith future strategies for disease management.